Aprendizaje basado en proyecto y los estilos de aprendizaje, en estudiantes del nivel primario de la Institución Educativa 60756 Claverito 2024 - Panduro Acosta, Pablo Oliver (2025)
The study's overarching goal is to ascertain, for third graders enrolled in a public elementary school in Iquitos, Peru, how well the Program Stimulating and Strengthening the Reading Habit (PSRH) achieves its stated goal of improving students' reading comprehension. The study used an applied research approach and used a quasi-experimental methodology. Data were acquired by administering a validated reading comprehension assessment test to a sample of 30 students, as determined by expert judgment. After implementing the program, the analysis of reading comprehension reveals a significant improvement in student performance. The average score on the reading comprehension test has increased by 4.67 points (15.00-10.33=4.67). Furthermore, there has been an increase of 7.5 points (17.22-9.72=7.5) in the critical dimension, an increase of 4.93 points (16.19-11.26=4.93) in the literal dimension and an increase of 3.21 points (13.08-9.87= 3.21) in the inferential dimension. In this way, the curriculum has shown statistical significance (p<0.05) in helping the kids of Claverito School improve their reading comprehension.